HD‐ZIP IV gene Roc8 regulates the size of bulliform cells and lignin content in rice - Sun, Jing; Cui, Xuean; Teng, Shouzhen; Kunnong, Zhao; Wang, Yanwei; Chen, Zhenhua; Sun, Xuehui; Wu, Jinxia; Ai, Pengfei; Quick, William Paul; Lu, Tiegang; Zhang, Zhiguo (Wiley, 2020)
The morphology of bulliform cells located on the upper epidermis of leaves is one of the most important cell structures affecting leaf shape. Although many mechanisms regulating the development of bulliform cells have been reported, the fine regulatory mechanisms governing this process have rarely been described. To identify novel components regulating rice leaf morphology, a mutant showing a constitutively rolling phenotype from the seedling stage to flowering, known as crm1‐D, was selected for further analysis. Anatomical analyses in crm1‐D were attributable to the size reduction of bulliform cells. The crm1‐D was controlled by a single dominant nuclear gene. Map‐based cloning revealed that Roc8, an HD zipper class IV family member, was responsible for the crm1‐D phenotype. Notably, the 50‐bp sequence in the 3′‐untranslated region (3′‐UTR) of the Roc8 gene represses Roc8 at the translational level. Moreover, the roc8 knockdown lines notably increased the size of bulliform cells. A series of assays revealed that Roc8 negatively regulates the size of bulliform cells. Unexpectedly, Roc8 was also observed to positively mediate lignin biosynthesis without incurring a production penalty. The above results show that Roc8 may have a practical application in cultivating materials with high photosynthetic efficiency and low lignin content.